The Effects of Smartphone, Tablet and Computer Overuse on Children’s Eyes During the COVID-19 Pandemic - Hakan Öztürk (Galenos Yayinevi, 2021)
Aim:Due to restrictions during the Coronavirus disease-2019 (COVID-19) pandemic, smartphone, tablet and computer (STC) overuse might occur. There were some concerns that light sources which emit blue light might affect anterior and posterior segment structures. We investigated the effects of STC overuse on children’s eyes during the pandemic.Materials and Methods:Sixty-four children’s findings at baseline (the early period of the pandemic) (group 1) were compared with those after 1 year (group 2). Correlations between daily STC use time (DSTCUT) and the ocular parameters in group 2 were evaluated.Results:Compared to group 1, group 2 had longer DSTCUT (1.49±0.33 vs 5.62±0.57 hours, p<0.001), lower tear break-up time (TBUT) (12.70±1.45 vs 9.50±2.10 seconds, p=0.015), higher ocular surface disease index (OSDI) score (14.52±4.19 vs 25.22±5.75, p=0.007), more myopic spherical equivalent refraction (SER) (-1.00±0.30 vs -1.80±0.40 dioptres, p=0.031), and greater axial length (22.69±0.43 vs 23.42±0.37 millimetres, p=0.038). Schirmer tests, central corneal thicknesses (CCT), keratometries, anterior chamber depths (ACD), lens thicknesses (LT), retinal nerve fibre layer thicknesses, choroidal thicknesses and macular thicknesses of groups were similar (p>0.05). In group 2 as DSTCUT increased, TBUT (r=-0.368, p=0.034) decreased, OSDI score (r=0.384, p=0.028) increased and more myopic SER (r=0.340, p=0.045) occurred.Conclusion:To our knowledge, this is the first study in children to comprehensively investigate the effects of STC overuse during a pandemic on ocular surface, anterior and posterior segment structures together. We found that STC overuse during the pandemic might increase the tendency to dry-eye and myopia, and might cause axial elongation. We also determined that at 1-year follow-up, STC overuse had no effect on CCT, keratometry, ACD, LT, and posterior segment parameters.